Complete Uterine Septum with Cervical Duplication and Longitudinal Vaginal Septum: An Anomaly Supporting Alternative Embryological Development - Arpita De; Abhinav Jain; Reva Tripathi; Aruna Nigam (Wolters Kluwer Medknow Publications, 2020)
The diagnosis and management of Mullerian abnormalities have revolutionized with the advent of magnetic resonance imaging, three-dimensional ultrasound, and endoscopic techniques. All the earlier unclassified abnormalities can now be classified as per the new European Society of Human Reproduction and Embryology 2013 nomenclature. The presence of complete uterine septum with cervical duplication and longitudinal vaginal septum reinforces the alternative theory of Mullerian development. The presence of this complex anomaly is discussed in the light of embryonic development along with management issues.